Editorial - Thomas D. Wilson (Information Research: An International Electronic Journal)
This is my final Editorial as Editor-in-Chief of Information Research. I hand over to Professor Crystal Fulton at the end of this month. It seems appropriate, then, to reflect on the history of the journal and to consider its future. I created the journal in 1995, when the World Wide Web was just beginning to make an impact. For a time the journal was housed on a server in the then Department of Information Studies (now the Information School) at the University of Sheffield. However, when I retired in 2000, it became evident that the future of the journal would be uncertain and so I moved it on to a commercial service, which had quite modest annual fees, which I paid myself. This continued until Lund University kindly offered to host the journal, and that arrangement continued until I gave the journal to the University of Borås in 2017.